2021
DOI: 10.1057/s41287-020-00352-2
|View full text |Cite
|
Sign up to set email alerts
|

Who Wants to Farm? Answers Depend on How You Ask: A Case Study on Youth Aspirations in Kenya

Abstract: While there is a consensus that rural poverty has to be reduced, there are two opposing views on the role that agriculture can play in this regard: a “farm-based” and an “off-farm led” development paradigm where the respective other sector is merely a complementary income source during a transition period. The latter paradigm is supported by studies finding that rural youth in sub-Saharan Africa are not particularly interested in agriculture. However, policy discourse on youth in agriculture often situates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…A study from Kenya reports 65% of the rural youth opted for having their own business rather than agriculture as their preferred livelihood option. However, LaRue et al (2021) concluded that artificially forcing youth to choose between alternative livelihood options may disguise nuanced aspirations as open ended questions revealed that most youth envision a mixed livelihood. Therefore, the continued importance and sustainability of the agricultural sector will rely on qualified and competent youth who can involve themselves in farming.…”
Section: Aging Farming Population Urban Migration and Agriculturementioning
confidence: 99%
“…A study from Kenya reports 65% of the rural youth opted for having their own business rather than agriculture as their preferred livelihood option. However, LaRue et al (2021) concluded that artificially forcing youth to choose between alternative livelihood options may disguise nuanced aspirations as open ended questions revealed that most youth envision a mixed livelihood. Therefore, the continued importance and sustainability of the agricultural sector will rely on qualified and competent youth who can involve themselves in farming.…”
Section: Aging Farming Population Urban Migration and Agriculturementioning
confidence: 99%
“…Our study also reveals that intrahousehold decisionmaking and labor dynamics vary with marital status and male absence associated with off-farm employment and outmigration. These findings contribute to a growing awareness that multiple social dimensions intersect with gender to shape men's and women's interest in, contribution to, and benefit from agricultural innovations (Carr and Thompson 2014), including age and position in household (Crossland et al 2021, LaRue et al 2021, wealth (Shibata et al 2020), and kinship structures (Meijer et al 2015).…”
Section: Changes In the Wider Social Context Of On-farm Restorationmentioning
confidence: 76%
“…The ratio of male to female household heads was almost identical in both groups (at 4:1) (Table 1). Given the emphasis in the migration literature on youth migration, the similarity in the age structure of migrant and non-migrant household heads is noteworthy [50][51][52]. In total, 40% of migrant household heads and 45% of non-migrant household heads were under the age of 35.…”
Section: Resultsmentioning
confidence: 99%